GERAK TANGAN SEBAGAI INSPIRASI DARI PERMASALAHAN SOSIAL DALAM BERKARYA SENI GRAFIS - Geo Sugiwang; Yofita Sandra (Universitas Negeri Padang, 2021)
The hands are also part of the intermediary result of human thinking that can create something new, to produce writings, making beautiful art because hand was channeling ideas and resources creative human so as to produce a shape With everything that can be done with a second hand that has given its role and its influence in life, the author wants to describe the things that give the meaning of the motion of the hands itself. through the technique of Stencil print in the process of work to be one of the options of making art graphics. After various observations as well as the work of a long contrivances 10 works of art can be shown that: : 1) Demi Sejengkal, 2) Tahan, 3) Lepas Tangkap, 4) Pemilih, 5) Tolong Tertolong, 6) Pandangan, 7) Hormat, 8) Pengendali, 9) Berjanji Mengingkari, 10) Batu,Gunting,Kertas.Keyword : Moving hand, Stencil Print